Population substructure and signals of divergent adaptive selection despite admixture in the sponge Dendrilla antarctica from shallow waters surrounding the Antarctic Peninsula. Issue 13 (25th June 2019) - Leiva, Carlos; Taboada, Sergi; Kenny, Nathan J.; Combosch, David; Giribet, Gonzalo; Jombart, Thibaut; Riesgo, Ana
Abstract: Antarctic shallow‐water invertebrates are exceptional candidates to study population genetics and evolution, because of their peculiar evolutionary history and adaptation to extreme habitats that expand and retreat with the ice sheets. Among them, sponges are one of the major components, yet population connectivity of none of their many Antarctic species has been studied. To investigate gene flow, local adaptation and resilience to near‐future changes caused by global warming, we sequenced 62 individuals of the sponge Dendrilla antarctica along the Western Antarctic Peninsula (WAP) and the South Shetlands (spanning 900 km). We obtained information from 577 double digest restriction site‐associated DNA sequencing (ddRADseq)‐derived single nucleotide polymorphism (SNP), using RADseq techniques for the first time with shallow‐water sponges. In contrast to other studies in sponges, our 389 neutral SNPs data set showed high levels of gene flow, with a subtle substructure driven by the circulation system of the studied area. However, the 140 outlier SNPs under positive selection showed signals of population differentiation, separating the central–southern WAP from the Bransfield Strait area, indicating a divergent selection process in the study area despite panmixia. Fourteen of these outliers were annotated, being mostly involved in immune and stress responses. We suggest that the main selective pressure on D. antarctica might be the difference in the planktonic communities present in the central–southern WAP compared to the Bransfield Strait area, ultimately depending on sea‐ice control of phytoplankton blooms. Our study unveils an unexpectedly long‐distance larval dispersal exceptional in Porifera, broadening the use of genome‐wide markers within nonmodel Antarctic organisms.